Ubiquitous Presence and Novel Diversity of Anaerobic Alkane Degraders in Cold Marine Sediments - Gittel, Antje; Donhauser, Jonathan; Røy, Hans; Girguis, Peter R.; Jørgensen, Bo B.; Kjeldsen, Kasper U. (Frontiers in Microbiology, 2015)
Alkanes are major constituents of crude oil and are released to the marine environment by natural seepage and from anthropogenic sources. Due to their chemical inertness, their removal from anoxic marine sediments is primarily controlled by the activity of anaerobic alkane-degrading microorganisms. To conduct a comprehensive cultivation-independent survey of the diversity and distribution of anaerobic alkane degraders, we designed novel PCR primers that cover all known diversity of the 1-methylalkyl succinate synthase gene (masD/assA), which catalyzes the initial activation of alkanes. We studied masD/assA gene diversity in pristine and seepage-impacted Danish coastal sediments, as well as in sediments and alkane-degrading enrichment cultures from the Middle Valley (MV) hydrothermal vent system in the Pacific Northwest. MasD/assA genes were ubiquitously present, and the primers captured the diversity of both known and previously undiscovered masD/assA gene diversity. Seepage sediments were dominated by a single masD/assA gene cluster, which is presumably indicative of a substrate-adapted community, while pristine sediments harbored a diverse range of masD/assA phylotypes including those present in seepage sediments. This rare biosphere of anaerobic alkane degraders will likely increase in abundance in the event of seepage or accidental oil spillage. Nanomolar concentrations of short-chain alkanes (SCA) were detected in pristine and seepage sediments. Interestingly, anaerobic alkane degraders closely related to strain BuS5, the only SCA degrader in pure culture, were found in mesophilic MV enrichments, but not in cold sediments from Danish waters. We propose that the new masD/assA gene lineages in these sediments represent novel phylotypes that are either fueled by naturally occurring low levels of SCA or that metabolize medium- to long-chain alkanes. Our study highlights that masD/assA genes are a relevant diagnostic marker to identify seepage and microseepage, e.g. during prospecting for oil and gas, and may act as an indicator of anthropogenic oil spills in marine sediments.